The SPICE Modeling of a Radiation Sensor Based on a MOSFET with a Dielectric HfO2/SiO2 Double-Layer - Miloš Marjanović; Stefan D. Ilić; Sandra Veljković; Nikola Mitrović; Umutcan Gurer; Ozan Yilmaz; Aysegul Kahraman; Aliekber Aktag; Huseyin Karacali; Erhan Budak; Danijel Danković; Goran Ristić; et al. (Sensors)
We report on a procedure for extracting the SPICE model parameters of a RADFET sensor with a dielectric HfO2/SiO2 double-layer. RADFETs, traditionally fabricated as PMOS transistors with SiO2, are enhanced by incorporating high-k dielectric materials such as HfO2 to reduce oxide thickness in modern radiation sensors. The fabrication steps of the sensor are outlined, and model parameters, including the threshold voltage and transconductance, are extracted based on experimental data. Experimental setups for measuring electrical characteristics and irradiation are described, and a method for determining model parameters dependent on the accumulated dose is provided. A SPICE model card is proposed, including parameters for two dielectric thicknesses: (30/10) nm and (40/5) nm. The sensitivities of the sensors are 1.685 mV/Gy and 0.78 mV/Gy, respectively. The model is calibrated for doses up to 20 Gy, and good agreement between experimental and simulation results validates the proposed model.